Ekonomski pomen naložb zasebnega lastniškega kapitala - Gabrič, Primož (LeXonomica, 2021)
The economic impact of private equity investments. Policy makers who aim to stimulate economic growth often attempt to create or expand their local venture capital industries. The main reason for these attempts is a conviction that venture capital spurs innovation and firm growth. On the other site private equity funded buy-outs have attracted particular criticism from trade unions and politicians, who accuse private equity of seeking to reduce employment costs and threatening jobs, working condition and training investments. This paper systematically reviews and analyses a majority of most important studies on economic impact of venture and buyout capital (private equity capital). The review and analyses of empirical studies show that venture capital investments have significantly positive impact on employment growth, human resources management, innovation, indebtedness and economic growth. There is no sufficient evidence on negative economic impact of buyout capital. On the contrary, buyout capital may be in some cases important economic factor for further firm development.Povzetek. Vlade različnih držav se pri poskusih spodbujanja gospodarske rasti večkrat poslužujejo tudi ukrepov, ki naj bi spodbudili trg tveganega kapitala. Glavni razlog za te spodbude leži v prepričanju, da tvegani kapital spodbuja inovacije in rast gospodarskih družb. Na drugi strani smo s strani sindikatov in politikov priča ostrim kritikam odkupov gospodarskih družb s pomočjo skladov zasebnega lastniškega kapitala, ki obtožujejo sklade zasebnega lastniškega kapitala zmanjševanja stroškov zaposlenih, ogrožanja delovnih mest, delovnih razmer in izobraževanja na delu. Prispevek sistematično predstavlja in analizira večji del najpomembnejših raziskav ekonomskega vpliva naložb tveganega in odkupnega kapitala (zasebnega lastniškega kapitala). Pregled in analiza empiričnih študij dokazujeta, da imajo naložbe tveganega kapitala posebno pozitiven vpliv na rast zaposlovanja, upravljanje s človeškimi viri, inovacije, zadolženost gospodarskih družb in gospodarsko rast. Prav tako ni trdnih dokazov o negativnem ekonomskem vplivu odkupnega kapitala. Nasprotno, odkupni kapital je lahko v nekaterih primerih pomemben ekonomski dejavnik za nadaljnji razvoj gospodarskih družb.
Keywords: venture capital; private equity capital; employment growth; innovation; indebtedness; economic growth